ANALISIS PENGARUH FAKTOR RISIKO KECURANGAN TERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar pada Bursa Efek Indonesia Periode 2011-2013) - Putri Rachmasari; Darsono Darsono (Diponegoro Journal of Accounting, 2015)
This study aims to analyze effect of fraud risk factors in fraud  triangle  for  earnings management. Fraud  triangle theory by Cressey (1953) states that three conditions applied for risks of  fraud; pressure, opportunity and  rationalization. Testing the  possibility of earnings management, study proposes variable as a proxy measure for three components of fraud triangle, as shown in SAS No. 99 namely personal financial need, and external pressure as a pressure component size, effectiveness of controls as a measure of opportunity component, and component rationalization. Population of this study is manufacturing companies listed in Indonesia Stock Exchange (BEI) for the period of 2011 to 2013. Purposive  sampling method is used to obtain data from 147 manufacturing  companies. Type of data are secondary. Hypotheses are tested using multiple linear regression. The results show that external pressure variable proxies with leverage  and  variable rationalization proxied with KAP has a  significant positive relationship with earnings management. Variables Personal financial need proxied by the ratio of share ownership by insiders and effectiveness of monitoring proxied by proportion of independent board has no effect on earnings management.